PENGARUH AROMATERAPI INHALASI LEMON TERHADAP PENURUNAN NYERI PERSALINAN KALA I FASE AKTIF - Siti Cholifah; Abkar Raden; Ismarwati - (Universitas Aisyiyah Yogyakarta, 2016)
This research to describe the effects of lemon aromatherapy inhalation on the reduction of first stage  labor pain in the active phase. The study was a quasi-experimental with pre-test-post-test non equivalent control group design. Mann-Whitney bivariable analysis and linear regression for multivariable analysis. The result of this study was average of labor pain in aromatherapy group was  4.74 + 1.327 wich is lower  than  control group 5.79 + 1.316. Result of Mann-Whitney test is  P 0.001 < 0.05. External variables which influence the labor pain was anxiety  with  the value of P < 0.05. There is inhaled lemon aromatherapy effect on reducing first stage labor pain  in active phase.   Keywords: lemon aromatherapy inhalation, labor pain, first stage, active phase